A Streetcar Named Desire : Disc 1-2 Special Features - Kazan, Elia, 1909-2003; Leigh, Vivien; Marlon Brando; Kim Hunter; Karl Malden; Rudy Bond; Nick Dennis; Peg Hillias; Wright King; Richard Garrick; Ann Dere; Edna Thomas; et al. (USA Charles K. Feldman Group, 1951)
Blanche is in real need of a protector at this stage in her life when circumstances lead her into paying a visit to her younger sister Stella in New Orleans. She doesn't understand how Stella, who is expecting her first child, could have picked a husband so lacking in refinement. Stanley Kowalski's buddies come over to the house to play cards and one of them, Mitch, finds Blanche attractive until Stanley tells him about what kind of a woman Blanche really is. What will happen when Stella goes to the hospital to have her baby and just Blanche and her brother-in-law are in the house?
Set in the French Quarter of New Orleans during the restless years following World War Two, A STREETCAR NAMED DESIRE is the story of Blanche DuBois, a fragile and neurotic woman on a desperate prowl for someplace in the world to call her own. After being exiled from her hometown of Auriol, Mississippi for seducing a seventeen-year-old boy at the school where she taught English, Blanche explains her unexpected appearance on Stanley and Stella's (Blanche's sister) doorstep as nervous exhaustion. This, she claims, is the result of a series of financial calamities which have recently claimed the family plantation, Belle Reve. Suspicious, Stanley points out that "under Louisiana's Napoleonic code what belongs to the wife belongs to the husband." Stanley, a sinewy and brutish man, is as territorial as a panther. He tells Blanche he doesn't like to be swindled and demands to see the bill of sale. This encounter defines Stanley and Blanche's relationship. They are opposing camps and Stella is caught in no-man's-land. But Stanley and Stella are deeply in love. Blanche's efforts to impose herself between them only enrages the animal inside Stanley. When Mitch -- a card-playing buddy of Stanley's -- arrives on the scene, Blanche begins to see a way out of her predicament. Mitch, himself alone in the world, reveres Blanche as a beautiful and refined woman. Yet, as rumors of Blanche's past in Auriol begin to catch up to her, her circumstances become unbearable.
Blanche Dubois goes to visit her pregnant sister and husband Stanley in New Orleans. Stanley doesn't like her, and starts pushing her for information on some property he know was left to the sisters. He discovers she has mortgaged the place and spent all the money, and wants to find out all he can about her. Even more friction develops between the two while they are in the apartment together...
...When she got there she met the brute Stan, and the side of New Orleans she hardly knew existed.
Keywords: Drama -- American Corner